LANGUAGE LEARNING STRATEGIES USED BY SCIENCE AND SOCIAL STUDENTS IN SMA BRAWIJAYA SMART SCHOOL MALANG - YUSTITIASARI, HILDA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Language Learning Strategies, Academic Major English is a compulsory subject in high school in Indonesia. Therefore, high school students should know and manage their strategies in learning English. For students in senior high school, their strategies should be suitable with their major because different major may influence the strategies applied. This present study is aimed at investigating the learning strategies of science and social students of SMA Brawijaya Smart School and the correlation between the academic major and language learning strategies.The approach used is quantitative study. The participants of this study were 113 students consisting of 71 science and 42 social students. The survey comprised an individual background questionnaire and Strategy Inventory for Language Learning (SILL) adopted from Oxford (1990).This study reveals that the students moderately employs the six categories of learning strategies in their learning process. This finding can be measured by the overall language learning strategies which fall into medium level. The result shows that metacognitive strategies are the most frequently used by the students whereas affective strategies are the lowest frequently used. Although there are differences in the mean score for the overall language learning strategies used by science and social students, the T- test result shows that there is no significant difference in language learning strategies applied by science and social students.In addition, Chi-square result shows that there is no significant correlation between different academic major and the choice of language learning strategies. In conclusion, science students apply language learning strategies more than social student and the strategies mostly applied from overall language learning strategies is metacognitive strategies. Also, there is no significant correlation between academic major and language learning strategies. Hence, in choosing the efficient strategies it is suggested that the learners apply appropriate language learning strategies based on student’s respective goals.